Contributions of teaching students to built a competent teacher profile from the reflexion in the classroom - Vicente Carrasco Embuena; Mª José Hernández Amorós; Marcos J. Iglesias Martínez (Ediciones Universidad de Salamanca, 2012)
This paper is the result of a study suggested to recognize what the profile of a good teacher is, by the identification and description of the qualities that students of Teaching Degree attribute them. The study is based on information provided by a group of 73 students of the second course of Teaching in Physical Education Degree, from the University of Alicante, of the academic course 2009/10. The students answered openly the proposal to write two letters to two of their teachers at any stage of their academic career: one was addressed to that teacher who had had a profound impact on them, the other, to that person dedicated to teaching but had gone unnoticed in their lives. We have focused our attention only at the letters that they addressed to good teachers because it has been considered the magnitude of the study. Participants have thrown valuable information that has become the engine of this research, qualitative in nature, with which we have studied a number of categories with AQUAD 6 (Huber, 2006) programme. The results contribute to draft the profile of a teaching professional to educate citizens in the information society, based in five dimensions: personal qualities of teachers, teaching ability, quality of teacher interaction processes, types of training promoted by the teacher and teacher performance impact on students. These dimensions are basically the same in the scientific literature and in the syllabus of Teaching Degree.